2016
DOI: 10.1614/wt-d-15-00096.1
|View full text |Cite
|
Sign up to set email alerts
|

Yield Loss and Management of Volunteer Corn in Soybean

Abstract: This book was published by iGrow, a service of SDSU Extension. For more information in the fields of agriculture, farming and rural living available in print, electronically, or on-line, visit iGrow.org.Information in this book is intended to be a guideline for label information, but not a label substitute. Pesticide product (herbicides, insecticides and fungicides) labels can change at any time. Applicators must follow label procedures when applying a pesticide product (herbicides, insecticides and fungicides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…Previous research also showed that volunteer corn growing in bean can be a highly competitive weed. Our results are consistent with those found by Alms et al (2016) that found i = 39.7, and Marquardt et al (2012b) observed i = 25, being these values obtained for the simultaneous emergence between volunteer corn and soybean. For dry bean, at each volunteer corn plant per square meter, the reduction on dry bean yield ranged from 6.5 at 19.3% (Sbatella et al, 2016).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Previous research also showed that volunteer corn growing in bean can be a highly competitive weed. Our results are consistent with those found by Alms et al (2016) that found i = 39.7, and Marquardt et al (2012b) observed i = 25, being these values obtained for the simultaneous emergence between volunteer corn and soybean. For dry bean, at each volunteer corn plant per square meter, the reduction on dry bean yield ranged from 6.5 at 19.3% (Sbatella et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…The high losses of bean yield due to the increase of volunteer corn density, agree with found by Alms et al (2016), which verified a maximum yield loss in soybean of 71% for three plants m -2 of volunteer corn. The interference effects on bean yield from weeds is lower than volunteer corn, where the impact of high density of E. heterophylla (23 plants m²) reduce 54% of bean yield (Machado et al, 2015) and maximum losses for different bean cultivars ranging from 15.4 to 43.6% (density ranging from 0 to 50 plants m²) in competition with Bidens pilosa (Galon et al, 2016).…”
Section: /7supporting
confidence: 89%
See 2 more Smart Citations
“…Lower soybean yields were likely due to competition from grassy weed species, which were not well controlled by the POST‐applied‐only treatments (Table 5). Several studies have demonstrated the competitive potential of grasses to reduce soybean yields (Alms et al, 2016; Guglielmini et al, 2016; Hock et al, 2006; Vail and Oliver, 1993).…”
Section: Soybean Yieldsmentioning
confidence: 99%